El aprendizaje significativo en neonatología es superior que el aprendizaje por el método tradicional (2013)
It is a critical analysis of neonatology rotation for pediatric residents and neonatal fellow from the description of the process of learning that takes place. This analysis highlights the positive changes in the teaching-learning process that have been taking place over time and proposes new challenges to optimize meaningful learning through a more reflective thinking.